The role innovative leadership in administrative empowerment (Study analysis of the views of a sample of decision makers in the General Company for Food Industries( - محمد, محمود شكر (Journal of Economics and Administrative Sciences, 2019)
AbstractThe objective of the research is to identify the role of innovative leadership in achieving the dimensions of administrative empowerment in the company for the public of food industries. The various variables have shown the importance of innovative leadership to achieve the dimensions of administrative empowerment in both international and local companies. Administrative Empowerment "In order to answer this question, a virtual model was developed to reflect the relationship and impact between innovative leadership and administrative empowerment. The research was based on the analytical descriptive approach.  the research community, The company represented the general company for food industries, retrieved form 48 represented a sample of departments and directors of the people by research found a number of the most important results, a correlation between the innovative relationship LeadershipAnd the administrative empowerment of the company investigated if the relationship is positive and strong, and reflected the results of a set of recommendations, the most important, the need to benefit the company investigated, the evaluation of the leaders of the company from time to time in order to achieve the dimensions of administrative empowerment